Analisis Kepercayaan Pengguna E-Money (Studi Pada Masyarakat di Wilayah Bandung Raya) - Ivon Sandya Sari Putri; Mudya Shegi Islamia (Jurnal Riset Bisnis dan Investasi, 2022)
The financial payment system has changed along with technological developments. One of them is electronic money or e-money. The benefits of e-money are considered important, especially during the Covid-19 pandemic where it is recommended to reduce physical contact in suppressing the spread of the Covid-19 virus. The level of use of e-money continues to increase, and even so, consumer trust, one of which is data security and e-money finance is still a matter of concern. This study aims to determine the trust of e-money users in the Greater Bandung area. Consumer trust is measured through four dimensions, namely benevolence, ability, integrity, and willingness to depend. The quantitative descriptive method is the research method used in this study by distributing questionnaires to 220 respondents. The results of this study suggest that the trust of e-money users in the Greater Bandung area is high.